A dual purpose aluminum-based metal organic framework for the removal of chloramphenicol from wastewater. (December 2022) - Geçgel, Cihan; Görmez, Özkan; Gözmen, Belgin; Turabik, Meral; Kalderis, Dimitrios
Abstract: The presence of antibiotics in the aquatic environment can cause significant environmental and human health problems even at trace concentrations. Conventional treatment systems alone are ineffective in removing these resistant antibiotics. To address this problem, oxidation and adsorption techniques were used to explore the removal of recalcitrant antibiotic chloramphenicol (CAP). An aluminum-based metal-organic framework (Al-MIL) with high surface area and extended porosity, was prepared and used both as adsorbent and catalyst for the oxidation of CAP. Characterization of the Al-MIL revealed a large surface area of 1137 m 2 g −1, a homogeneous microporous structure, good crystallinity, and particle size in the range of 200–400 nm. Adsorption of CAP on Al-MIL achieved equilibrium after 1 h, reaching a maximum adsorption capacity of 96.1 mg g −1 at the optimum pH value of 5.3. The combination of adsorption and oxidation did not improve the % TOC reduction considerably, indicating an antagonistic rather than synergistic effect between the two processes. Oxidation alone in the presence of persulfate, achieved a % TOC reduction of 71% after 2 h, compared to 56% achieved by adsorption alone at the same duration. The optimum persulfate concentration was determined as 2.5 mM. The Al-MIL structure did not demonstrate any substantial deterioriation after six repeated runs, according to the reusability experiments. Highlights: A simple, microwave-assisted synthesis of aluminum-based MOF is reported. Al-MIL acted both as adsorbent and as a catalyst in chloramphenicol removal. The optimum adsorption capacity of Al-MIL was 96.1 mg g −1 at pH 5. Oxidation achieved a total organic carbon reduction of 71%. The combination of adsorption and oxidation showed an antagonistic effect.